Pengembangan Alat Penyaring Tahu Yang Ergonomis Menggunakan Metode EFD - Delvin Ramadhani; Sanny Hahury; Masniar (Industrial Engineering Journal – System, 2023)
The screening stage of tofu in the Independent Cooperative (UKM) is still done manually so this research was conducted to develop an ergonomic tofu filter tool, in order to simplify and reduce the filtering process time and to increase the amount of production per day. Data was collected through observation, interviews, questionnaires, documentation and literature studies. Ergonomic Function Deployment (EFD) is the development of Quality Function Deployment (QFD), namely by adding a new relationship between consumer desires and product ergonomic aspects. This relationship will complete the form of the House of Quality matrix which also translates into the desired ergonomic aspects. The House of Quality matrix used in EFD was developed into a House of Ergonomic matrix which was refined with an anthropometric approach. from the results of the validity test the value is 0.917 and the reliability value is obtained cronchbach''s alpha 0.923, efd data processing results from the total value of the result determines the level of consumer interest, namely 39.83 and the total value of the result determines the level of customer satisfaction 40.33, the largest result from the total improvement ratio value of 8.97, the result of the total raw weight value is 59.5 and the result of the normalized raw weight value is 1. From the processing of the Ergonomic Function Deployment method, the priority variable for product design is an ergonomic tofu filter tool with measuring 165cm high x 76.59 cm wide and 75.07 cm long, using an automatic propulsion machine and a machine for pumping water, helps workers produce production faster and can avoid worker injuries due to spills of hot tofu water.